2018
DOI: 10.1021/acs.molpharmaceut.8b00382
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Peyer’s Patch Uptake as a Strategy for Targeted Lung Delivery of Polymeric Rifampicin Nanoparticles

Abstract: Uptake of nanoparticles through Peyer's Patches following oral administration could enable translocation through lymph to lymphatic organs like the lungs. An important consideration, however, is nanosize and particle hydrophobicity. Furthermore, as delivering the nanoparticles to the intestine where the Peyer's Patches are localized is important, their intact and rapid transit through the stomach into the intestine is highly desirable. We report hydrophobization of mucoadhesive Rifampicin-GantrezAN-119 nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Hence considering strategies to enhance bioavailability could be an important approach to enhance efficacy at possibly lower doses ( Omolo et al, 2020 ). Furthermore, directing the drug in high concentration to the target site following oral administration could be achieved by lymphatic targeting of oral particulate carriers ( Bachhav et al, 2018 , 2017 ). With the myriad targets the drug exhibits potential to attack in the pathogenesis of COVID-19, let us hope it is the panacea the world seeks to overcome the fatality and the fear of COVID-19.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Hence considering strategies to enhance bioavailability could be an important approach to enhance efficacy at possibly lower doses ( Omolo et al, 2020 ). Furthermore, directing the drug in high concentration to the target site following oral administration could be achieved by lymphatic targeting of oral particulate carriers ( Bachhav et al, 2018 , 2017 ). With the myriad targets the drug exhibits potential to attack in the pathogenesis of COVID-19, let us hope it is the panacea the world seeks to overcome the fatality and the fear of COVID-19.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…However, at pH 6.8 sustained release of CUR from ISCurNP was observed upto 24 hr with maximum 46.6% release while free CUR demonstrated of 28.09% release (Supporting Information Figure S6). We have previously observed that hydrophilic NPs show gastric tropism while hydrophobic NPs favor intestinal accumulation. Such intestinal accumulation could favor high uptake of intact NPs through M cells of Peyer's patches followed by translocation through the lymph into systemic circulation .…”
Section: Resultsmentioning
confidence: 99%
“…119,120 The gastrointestinal localization and paracellular or lymphoid transport can be improved by adjusting the molecular weight, hydrophobicity, and adhesion of polymers. 121,122 As a natural cationic polysaccharide, chitosan (CS) has been used for the delivery of small molecules, proteins, polypeptides, polysaccharides, and genes. [123][124][125] At the same time, many chitosan derivatives with better delivery properties have been developed such as trimethyl chitosan, carboxymethyl chitosan, and thiolated chitosan, all of which played an important role in the development of oral drug delivery systems.…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%
“…As a result, the relative bioavailability of rifampicin-Gantrez-ethylcellulose nanoparticles nearly tripled, and more drugs accumulated in lung. 122 Helicobacter pylori is a micro-aerobic gram-negative bacterium that colonizes the deep layer of human gastric mucus with acidic pH values. 135,136 Therefore, therapeutic agents not only need to penetrate the gastric mucus layer but also need to be protected from the acidic environment.…”
mentioning
confidence: 99%